The Effect of Cognitive Emotion Regulation on Job Satisfaction - Seyed Mehdi Alvani; Gholamreza Memarzadeh; Somayeh Shahba (مطالعات مدیریت بهبود و تحول, 2017)
The Present study has examined the effects of cognitive emotion regulation on job satisfaction of employees. In this survey, the questionnaires were distributed among sample of staff employees of the Islamic Republic of Iran Customs Administration. In order to assess construct validity and reducing measurement error, multidimensional item- response theory was applied. The result revealed that most items showed good discriminative power. Some items were removed according to low factor score. Nevertheless, according to exploratory factor analysis and identifying item parameters based on item-response theory, questionnaires had reported appropriate validity and reliability. In addition, some adjusted cognitive emotion regulation strategies include acceptance, positive reappraisal, planning and positive refocus caused   increasing job satisfaction of employees but there is no relationship between put into perspective and job satisfaction. Moreover, unadjusted cognitive emotion regulation strategies (self-blame, other-blame and catastrophizing) reduce employees' job satisfaction.